2021
DOI: 10.5435/jaaos-d-21-00732
|View full text |Cite
|
Sign up to set email alerts
|

Modified Weaver-Dunn Technique Using Transosseous Bone Tunnels and Coracoid Suture Augmentation

Abstract: Introduction: A modified Weaver-Dunn procedure for the management of acromioclavicular joint injuries that uses transosseous bone tunnels and coracoid suture augmentation is described with associated clinical results. Methods: A retrospective review of 39 consecutive patients who underwent a primary mWD procedure by a single surgeon from January 2013 to July 2019 was conducted. Patient charts and radiographs were reviewed for clinical course, complications and management, and radiographic evaluation. Satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…And there is also a problem that the steel plate needs to be removed through a secondary surgery [22]. The Weaver-Dunn technique is to reconstruct the CC ligament by transposition of the coracoacromial ligament to the distal end of the clavicle for the treatment of AC joint dislocation [22][23][24]. However, biomechanical studies have shown that the coracoacromial ligament has only 25% of the biomechanical strength of the CC ligament [22].…”
Section: Discussionmentioning
confidence: 99%
“…And there is also a problem that the steel plate needs to be removed through a secondary surgery [22]. The Weaver-Dunn technique is to reconstruct the CC ligament by transposition of the coracoacromial ligament to the distal end of the clavicle for the treatment of AC joint dislocation [22][23][24]. However, biomechanical studies have shown that the coracoacromial ligament has only 25% of the biomechanical strength of the CC ligament [22].…”
Section: Discussionmentioning
confidence: 99%